Block Chain Technology in Supply Chain Management Using Key Generation - et. al., Priti Lale, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An information system is very important in today's changing world, and therefore choosing the proper system is becoming a very important decision. With the time, the information systems have become more crucial, with multiple problems affecting the supply chain and the continuous writing of performance areas. The principle of chain management aims at chain values. The working of chain management states that chain management enhances the value of the chain by establishing operational units. Traditional manufacturing supply chains bear a lot from additional, costs, delays and information loss due to information middleware’s. Therefore, we propose a blockchain oriented supply chain architecture to reduce intrusion in traditional ones. Current approaches to private-key security include signature schemes based on bio-metrics, index-hidden private key design, and post-quantum block chain schemes. Nevertheless, recovering the lost private key is difficult in all approaches. Here we proposed an optimal key formation procedure using a fitness-based self-adaptive sea lion algorithm for secure information sharing in SCM using block chain.